2005
DOI: 10.1001/jama.294.24.3093
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Oral Amiodarone for the Prevention of Arrhythmias That Begin Early After Revascularization, Valve Replacement, or Repair

Abstract: Oral amiodarone prophylaxis of atrial tachyarrhythmias after cardiac surgery is effective and may be safe overall and in important patient subgroups. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT00251706.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(195 citation statements)
references
References 44 publications
7
179
0
9
Order By: Relevance
“…As shown by several RCTs and meta-analyses [183,184,186], amiodarone is effective for the prophylaxis of AF. The largest RCT reported atrial tachyarrhythmias in 16.1% of amiodarone-treated patients compared with 29.5% of placebo-treated patients (HR 0.52, 95% CI 0.34 0.69), a 13.4% absolute risk reduction [184]. However, amiodarone trials excluded patients with low resting heart rate, second or third degree atrioventricular block, or New York Heart Association (NYHA) class III or IV.…”
Section: S28 Esc/eacts Task Force On Myocardial Revascularization / Ementioning
confidence: 98%
See 1 more Smart Citation
“…As shown by several RCTs and meta-analyses [183,184,186], amiodarone is effective for the prophylaxis of AF. The largest RCT reported atrial tachyarrhythmias in 16.1% of amiodarone-treated patients compared with 29.5% of placebo-treated patients (HR 0.52, 95% CI 0.34 0.69), a 13.4% absolute risk reduction [184]. However, amiodarone trials excluded patients with low resting heart rate, second or third degree atrioventricular block, or New York Heart Association (NYHA) class III or IV.…”
Section: S28 Esc/eacts Task Force On Myocardial Revascularization / Ementioning
confidence: 98%
“…b-blockers, sotalol, and amiodarone reduce the risk of post-operative AF [183,184]. There is a wealth of safety and efficacy data, including two recent meta-analyses, supporting the routine use of b-blockers in post-operative cardiac surgical patients to reduce the incidence of post-operative AF (OR 0.36, 95% CI 0.28 0.47) [185,186].…”
Section: S28 Esc/eacts Task Force On Myocardial Revascularization / Ementioning
confidence: 99%
“…The lack of mechanistic cellular insight into the genesis of oxidative AF hampered the development of effective pharmacological therapy to suppress and/or prevent the oxidative AF [11]. For example, beta-blockers [12] and Amiodarone, [13] considered first line preventive drugs against POAF, are only partially effective. Interestingly, both human and animal studies have shown increased atrial CaMKII activity as the molecular signal that couples oxidative stress with AF [10].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The largest trial in cardiac surgery patients is the Prophylactic Oral Amiodarone for the Prevention of Arrythmias that Begin Early After Revascularization, (PAPABEAR) Valve Replacement, or Repair study. 7 In this randomized, double-blind, placebo-controlled trial, 601 patients undergoing CABG surgery, valve replacement/repair, or both, were randomized to receive oral amiodarone or placebo, starting 6 days prior to surgery and continuing for 6 days postoperatively. More than half the patients in each treatment group also received preoperative beta-blockers.…”
Section: Introductionmentioning
confidence: 99%